Data science : theory, analysis, and applications - Memon, Qurban A. (Qurban Ali); Khoja, Shakeel Ahmed (Boca Raton : CRC Press, 2020)
"The aim of this book is to provide an internationally respected collection of scientific research methods, technologies and applications in the area of data science. This book can prove useful to the researchers, professors, research students and practitioners as it reports novel research work on challenging topics in the area surrounding data science. In this book, some of the chapters are written in tutorial style concerning machine learning algorithms, data analysis, information design, infographics, relevant applications, etc. The book is structured as follows: Part 1: Data Science: Theory, Concepts, and Algorithms This part comprises five chapters on data Science theory, concepts, techniques and algorithms. Part II: Data Design and Analysis This part comprises five chapters on data design and analysis. Part III: Applications and New Trends in Data Science This part comprises four chapters on applications and new trends in data science"--
OCLC-licensed vendor bibliographic record.
Keywords: Data mining -- Statistical methods; Big data -- Statistical methods; Quantitative research; COMPUTERS / Database Management / Data Mining; TECHNOLOGY / Electricity; TECHNOLOGY / Electronics / General